Short versus long cephalomedullary nails for intertrochanteric femur fractures: A meta-analysis of randomized controlled trials - Shengquan Zhang; Qiaofeng Guo; Kai Huang; Haiqun Zhu (PLoS ONE, 2025)
Purpose We aim to evaluate the efficacy and safety of short cephalomedullary nails(CMN) versus long CMN in patients with intertrochanteric femur fractures(IFFs). Methods The PubMed, Web of Science, and Embase databases were searched for relevant publications until July 2024. All randomized controlled studies evaluating the efficacy and safety of short CMN versus long CMN in patients with IFFs were included. We estimated the pooled risk ratio (RR) with 95% confidence intervals (CIs) for binary outcomes, and the mean difference (MD) for continuous outcomes. Results A total of 7 studies with 658 patients were included in this analysis. There was no significant difference between the short CMN group and the long CMN group in Harris hip score, mortality within 1-year, overall complication rates, or reoperation rates. However, durations of surgery were significantly lower in the short CMN group compared to the long CMN group (MD: ‒21.83 minutes, 95% CI: ‒27.54 minutes, ‒16.13 minutes), along with significantly lower intraoperative blood loss (MD: ‒136.70 mL, 95% CI: ‒139.06 mL, ‒134.34 mL) and tip-apex distance (MD: ‒0.47 cm, 95% CI: ‒0.63 cm, ‒0.31 cm). There was also no significant difference in peri-implant fracture or lengths of hospital stays. Conclusions Short CMN are associated with shorter duration of surgery, reduced tip-apex distance, and lower intraoperative blood loss compared to long CMN for the fixation of IFFs. However, there were no significant differences in functional outcomes, overall complication rates, reoperation rates, mortality within one year, peri-implant fracture, or lengths of hospital stays.